PENGARUH KUALITAS TATA KELOLA PERUSAHAAN TERHADAP KOS KAPITAL SAHAM SYARIAH DI BURSA EFEK INDONESIA - Uswatun Hasanah (Jurnal Riset Akuntansi Soedirman (JRAS), 2022)
Corporate governance (CG) is a key differentiating factor that influences a company's readiness to enter the capital market, including the ASEAN integrated capital market. CG is also a measure for investors to participate in creating shareholder value, both for companies consisting of Islamic and conventional stocks. Shareholder value can be created through the influence of CG on the cost of capital (CoC). This study aims to examine the differences in the quality of corporate governance of Islamic and conventional stock issuers, as well as examine the effect of the quality of corporate governance on the cost of capital of Islamic stocks and conventional stocks. This study uses a sample of companies from all non-financial industries listed on the IDX which were selected using a purposive sampling technique. Data analysis uses panel data and hypothesis testing uses the t test. The test results show that 1) the quality of corporate governance of issuers of Islamic stocks is statistically better than the quality of corporate governance of conventional stock issuers, and 2) the effect of corporate governance on the cost of capital of issuers of Islamic stocks is statistically not stronger than the effect of corporate governance on cost of capital of conventional stock issuers. Thus, this study contributes to the corporate governance literature and the Islamic capital market literature.